Reducing Economics Test Anxiety among Students as Measured by a Test Anxiety Scale: A Cognitive Behavioural Therapy - Amedu, Amos Nnaemeka (Journal of Economics Education and Entrepreneurship, 2024)
Psychological problems such as anxiety have been reported to adversely affect students' learning outcomes.  This study explored the effectiveness of cognitive therapy with reflective activities on reducing Economics test anxiety among secondary school students. A randomizedcontrolledtrial experimental design was used. The sample sizewas120 senior secondary school students in South East Nigeria.A questionnaire titled "test anxiety scale" was used to collect data. It contained a demographic section and 20 items.To assign subjects to treatment or control groups, a randomization process was used.Subjectsin the treatmentgroup were subjectedto a cognitivebehavioural therapy (CBT) program.A three-time point evaluation was conducted with subjects in the treatment and control groups.Repeated measures and data collected were analysed with ANOVA. In comparison with the control group, research subjects exposed to CBT reportedlower testanxiety. In addition, at the follow-upmeasure, the scoresof researchsubjectsin the CBT groups weresignificantly lowerthan those of the control group. Hence,CBT significantly reducedEconomics students’ test anxiety. Theresearchers concludedthat the CBTprogramreducesEconomics students' test anxiety.